Teaching About Gender and Work: Using Case Studies for Team Projects - Bach, Rebecca (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The course that I developed, Gender, Work and Organizations, was created to serve as both an elective for the Sociology major and an elective in the interdisciplinary certificate program,Markets and Management Studies. The approach in the M&M certificate program tends to bevery applied and practical. And, students are generally encouraged to have real world experience in team projects. With these factors in mind, I developed a case study project. The cases used for the project are drawn from actual court cases or from fictional cases found in either a case studies text (Konrad, Alison, Cases in Gender and Diversity in Organizations; DeLaat, Jacqueline, Gender in the Workplace: A Case Study Approach, etc.) or from one of the online case clearinghouses (e.g. The European Case Clearing House).